Tracking and Blurring the Face in a Video File - Al-Mukhtar, Farah Saad (Al-Nahrain Journal of Science, 2018)
This paper shows how to detect, track and blur a face in video frame using the Viola-Jones detection algorithm for detection and KLT algorithm to tracks a set of feature points across the video frames. First, the detection locates the face, and then identifies feature points that can be reliably tracked.A blurring filter is applied after detection and tracking the face and very good results are obtained that can be useful to blurring the face; for example, when showing a painful view that includes distorted faces in wars reports or crimes.